Optimalisasi Pengelolaan Sampah Di Kelurahan Silae Kota Palu - Hijriah, Sri Aminah; Rivai, Abdul; Samsu, M. Kafrawi Al-Kafiah; Sahido, Samsu A. (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
The purpose of this study is to describe the results of the waste management program in Silae Village, Palu City. This type of research is descriptive and the basis of the research used is qualitative. In this study the author uses the Triple Bottom Line theory by (Jhon Elkinton 1997) with 3 indicators, namely profit, people, and planet (environment). Informants in this study consisted of employees of the Palu City environmental service, Silae Village staff, 2 TPS 3R managers and 3 community members. Data collection techniques were observation, interviews, and documentation. The collected data were filtered and selected based on data needs using qualitative descriptive methods. Based on the results of the study obtained, waste management in Silae Village has not been running optimally as can be seen from the indicators of profit, people, and planet (environment) where it can provide additional income for the community through the waste bank program. However, the perceived economic benefits are still limited due to the lack of skills and understanding in sorting waste, which results in managers having to purchase additional raw materials for compost production, community participation in waste management is still low. Even though the government has made every effort to provide outreach and education to the public, in reality there are still many people who do not understand and apply it in their daily lives.